Educação das relações étnico-raciais e a formação de professores - Tomasoni, Maria Lucia de Almeida Belem (2008)
This dissertation is linked to the Educational Policy of the Postgraduation Program in Education, based on law 10.639/03, which made obligatory the teaching of Afro-Brazilian History and Culture in all basic teaching school. The aim of this investigation is to analyze the Law under the Brazilian cultural and socio-historical context, the possibilities of implementation and its limits; to make a profound study of the work of forming teachers who deal with this discipline; and to analyze the conflicts of ethnical and racial nature, which are present in the discussion and implementation of the Law. This investigation is of bibliographic-documental nature and also involves a participative observation through a case study with public teachers of the State of Mato Grosso, in a city called Sinop. By accompanying the continuous formation of the teachers, records were made on how they reacted during it